PENGARUH TINGKAT KEPATUHAN GOVERNMENT REGULATIONS TERHADAP KINERJA KEUANGAN DENGAN VARIABEL CORPORATE SOCIAL RESPONSIBILITY DAN INOVASI SEBAGAI VARIABEL MEDIASI (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS BEI) - Niluh Komang Kusuma Yasari; Heri Pratikto; Ery Tri Djatmika Rudijanto Wahju Wardhana (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the effect of the level of compliance with government regulations on financial performance, with Corporate Social Responsibility (CSR) and innovation as mediating variables in Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange. This research employs an explanatory quantitative approach using secondary data obtained from financial statements, sustainability reports, and PROPER data from the Ministry of Environment and Forestry for the period 2021–2024. The sample consists of 35 companies with a total of 140 observations selected through purposive sampling. The variable of regulatory compliance is measured using PROPER scores, CSR is measured using a disclosure index based on GRI or POJK No. 51/POJK.03/2017, innovation is measured using the ratio of capital expenditure to total assets, and financial performance is measured using Return on Invested Capital (ROIC). Data analysis is conducted using SEM-PLS with the assistance of SmartPLS 4.0. The results indicate that the level of compliance with government regulations does not have a direct effect on financial performance, but has a positive effect on CSR and innovation. CSR does not affect financial performance and is unable to mediate the relationship between regulatory compliance and financial performance. In contrast, innovation has a positive effect on financial performance and is able to mediate the effect of regulatory compliance on financial performance. These findings suggest that regulatory compliance is more effective in improving financial performance when accompanied by innovation investments that enhance efficiency and competitiveness.